Three-Dimensional Avian Hematopoietic Stem Cell Cultures as a Model for Studying Disease Pathogenesis - Zmrhal, Vladimir; Svoradova, Andrea; Batik, Andrej; Slama, Petr (Frontiers in Cell and Developmental Biology, 2022)
Three-dimensional (3D) cell culture is attracting increasing attention today because it can mimic tissue environment and provide more realistic results than do conventional cell cultures. On the other hand, very little attention has been given to using 3D cell cultures in the field of avian cell biology. Although mimicking bone marrow niche is a classic challenge of mammalian stem cells research, experiments have never been conducted in poultry on preparing in vitro bone marrow niche. It is well known, however, that all diseases cause immunosuppression and target on immune cells and their development. Haematopoietic stem cells (HSC) reside in bone marrow and constitute a source for immune cells of lymphoid and myeloid origin. Disease prevention and control in poultry is facing new challenges, such as greater use of alternative breeding systems and expanding production of eggs and chicken meat in developing countries. Moreover, the COVID-19 pandemic will draw greater attention to the importance of disease management in poultry because poultry constitute a rich source of zoonotic diseases. For these reasons, and because they will lead to a better understanding of diseases pathogenesis, in vivo HSC niches for studying disease pathogenesis can be valuable tools for developing more effective disease prevention, diagnosis, and control. The main goal of this review is to summarize knowledge about avian haematopoietic cells, HSC niche, avian immunosuppressive diseases, isolation of HSC and main part of the review is dedicated to using of three-dimensional cell cultures and their possible use for studying disease pathogenesis with practical examples. Therefore, this review can serve as a practical guide to support further preparation of 3D avian HSC niche to study pathogenesis of avian diseases.